Pattern of surgical antibiotic prophylaxis in a tertiary care teaching hospital in India - Rehan, Harmeet Singh; Kakkar, Ashish Kumar; Goel, Shipra (International Journal of Infection Control, 2009)
Appropriate antibiotic prophylaxis can reduce the risk of postoperative wound infections, but misuse and overuse of antimicrobials increases both the cost and the selection pressure favoring the emergence of resistant bacteria. Our main objective was to study the pattern of prophylactic antibiotics in different surgeries in a large tertiary care teaching hospital. A total of hundred patients undergoing surgery, admitted under various hospital departments were enrolled in this prospective observational study. Pretested proforma which included information on patient characteristics, choice of antimicrobial agents as well as their route, timing and total duration of administration were completed. Also the appropriateness of antibiotic prophylaxis was assessed as per standard guidelines. It was found that the third generation cephalosporins were the most commonly prescribed class of antibiotics. Although only 67 percent cases required prophylaxis, it was administered in 86 percent of procedures, being unjustified in 19 % of cases. Mean timing of administration of antibiotics was 3.22 ± 1.03 hours prior to surgery and the patients received post operative antibiotics for a mean duration of 5 days during their stay in the hospital. Thus, surgical prophylaxis was inappropriate in terms of choice of agent, timing of administration as well as the total duration of prescription in majority of the cases. Interventions are warranted to promote the development, dissemination and adoption of evidence based guidelines for antimicrobial prophylaxis.